The reading habits of first-semester diploma UiTM students in Sarawak campus / Roselind Wee ... [et al.]. - Wee, Roselind; Sim Phek Kim, Jacqueline; John Jingut, Robert (2003)
This study was done to investigate the reading habits of 543 first-semester Diploma students by determining how much time per week they spent on reading and examining the reasons for their choice of reading materials. It was found that the majority of the subjects regardless of their family background or programmes that they were in were motivated to read. However, it was discovered that the subjects' motivation to read was very much influenced by the family buying reading materials. Reading to gain knowledge ranked as the most important reason for reading among the subjects.